2012
DOI: 10.1258/ebm.2012.012131
|View full text |Cite
|
Sign up to set email alerts
|

Human periprostatic white adipose tissue is rich in stromal progenitor cells and a potential source of prostate tumor stroma

Abstract: A body of growing evidence now implicates white adipose tissue as a relevant source of stromal progenitor cells recruited to the tumor microenvironment to form supportive tumor stroma. While the role of periprostatic (PP) adipose tissue in prostate cancer progression has been barely appreciated, we sought to determine the progenitor cell population in PP adipose tissue and the association with prostate cancer. We isolated and characterized CD31(-)CD34(+)CD45(-)CD146(-) progenitor cells (adipose-derived stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Increased number of circulating ASCs was first linked to cancer-free obese individuals by Bellows et al (70). Similar observations were reported for obese colorectal and prostate cancer patients (69, 71). In this regard, our finding of circulating ASCs among obese breast cancer survivors further validates the previous reports and extends the association between circulating ASCs and obesity to a women's cancer type that has been long associated with obesity.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Increased number of circulating ASCs was first linked to cancer-free obese individuals by Bellows et al (70). Similar observations were reported for obese colorectal and prostate cancer patients (69, 71). In this regard, our finding of circulating ASCs among obese breast cancer survivors further validates the previous reports and extends the association between circulating ASCs and obesity to a women's cancer type that has been long associated with obesity.…”
Section: Resultssupporting
confidence: 89%
“…Accrual of obese women with no history of breast cancer would shed light on this important question. Lastly, despite the common immunophenotype shared by circulating ASCs and their adipose tissue-derived counterparts, it was difficult to pinpoint the true origin of circulating ASCs as detected in the current and previously published studies (69-71). Comparison of the gene expression signature between these two sources of human ASCs, preferably from the same individual, may reveal additional commonality and potential distinctions between these two cell populations.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Although ASCs are primarily localized to fat depots, circulating ASCs have also been detected in obese individuals and cancer patients, with greater levels observed in obese patients bearing colon, prostate, or breast cancers (relative to lean) (142, 327, 367, 462). Additionally, relative to ASCs from lean adipose, ASCs isolated from obese adipose show enhanced potential to traffic to breast tumors in both humans and mice (366, 464).…”
Section: Microenvironmental Links Between Adipose Tissue and Cancermentioning
confidence: 99%
“…Ribiero et al observed higher levels of circulating ASCs in the blood of overweight or obese compared to lean prostate cancer patients (327). The authors also reported that periprostatic adipose tissue of prostate cancer patients bore significantly higher numbers of ASCs than nearby visceral adipose tissue, independent of BMI.…”
Section: Microenvironmental Links Between Adipose Tissue and Cancermentioning
confidence: 99%